Optimalisasi Peran Pemerintah Daerah Dalam Memberikan Fasilitas Penyelenggaraan Pondok Pesantren di Salafiyah Syafi’iyah Situbondo - Dairani Dairani (Hakim, 2023)
The birth of the Islamic Boarding School Law Number 18 of 2019 provides a breath of fresh air for the world of education and Islamic boarding school institutions. Apart from the birth of this law, Islamic boarding school institutions have become stronger and juridically legal because they have their own legal umbrella and apart from this, good things will also have an impact on graduates. or students whose legality is recognized and equalized, such as Ma'had Aly, for example. In terms of funding, Islamic boarding school institutions cannot be separated from the government's attention so that in the provisions of Articles 46 and 48, the Central Government and Regional Governments are obliged to participate in providing services and facilitating activities organized by Islamic boarding schools. The local government is also obliged to provide assistance in terms of human resource development in the Islamic boarding school environment, one of which is the object of research for this article is PP Salafiyah Syafi'iyah Sukerjo or commonly abbreviated as P2S3. From the results of this research, it is stated that the independence and development of the P2S3 Islamic boarding school is extraordinary even though previously there was no regional government intervention. It is hoped that the Situbondo Regional Government can immediately finalize the Regional Regulation on Islamic Boarding Schools so that in acting and providing service facilities there are standard procedures and in accordance with the provisions of laws and regulations, especially Law 18 of 2019 concerning Islamic Boarding Schools.